Garcinia gamblei (Clusiaceae), a new species from the southern Western Ghats, India - Shameer, Peerumuhammed Subaida; Sabu, Thyagarajan; Mohanan, Narayanan Nair (Phytotaxa, 2017)
Garcinia gamblei, a new species of Garcinia from Ponmudi Hills, southern Western Ghats of India is described and illustrated. The new species is allied to G. pushpangadaniana another endemic species of southern Western Ghats.